Investigation of effective thermal conductivity of SiC foam ceramics with various pore densities - Wang Enyu; Shi Zhongtian; Chen Miaomiao; Tang Shiqian; Zhang Xiangyu; Zhang Wei (Open Physics, 2022)
SiC foam ceramics are extensively used in numerous industrial applications that require high-temperature conditions. They can be used as thermal insulation, structural catalyst supports and energy storage materials. In this article, effective thermal conductivity of SiC foam ceramics at high temperature is studied by steady plane heat source method. This research aims to investigate the variations of effective thermal conductivity with pore density, stacking thickness, heat source temperature, and pore arrangement structure of foam ceramics. By a comparison of effective thermal conductivities of various pore density ceramic sheets, the experimental results show that the effective thermal conductivity of foam ceramics decreases with the increase of the pore density and stacking thickness. The effective thermal conductivity of the foam ceramics increases significantly when the heat source temperature is more than 200°C. For modular SiC foam ceramics, increasing the average pore density and sudden change of the pore density between ceramic sheets are not conducive to the increase of the effective thermal conductivity.